Determinasi Produktivitas Aircrew: Study Library Research - Esti Liana; Primadi Candra Susanto; Siska Yuli Anita; Indra Nuryanneti (JURNAL RISET MANAJEMEN (JURMA), 2026)
Flight crew productivity is a strategic factor in maintaining flight safety, operational efficiency, and airline competitiveness in the high-reliability aviation industry. This study aims to analyze and synthesize factors influencing flight crew productivity through a conceptual approach based on literature review. The research method used is library research with a systematic literature review technique. The type of data used is secondary data in the form of scientific articles, proceedings, and relevant previous research reports. Data sources were obtained from scientific databases such as Scopus, EBSCO, Copernicus, and SINTA. The results of the study indicate that adequate individual capabilities, a high level of work engagement, a measurable KPI system, and a fair and competitive remuneration scheme have a positive relationship with increasing aircrew productivity. Managerial implications emphasize the importance of designing integrated human resource policies, particularly in competency development, a safety- and efficiency-based performance appraisal system, and compensation management oriented towards sustainable performance.